Global conformation of Tau protein mapped by Raman spectroscopy - Gorantla, N.V.; Khandelwal, P.; Poddar, P.; Chinnathambi, S. (Methods in Molecular Biology, 2017)
Alzheimer’s disease (AD) is one of the neurodegenerative disease characterized by progressive neuronal loss in the brain. Its two major hallmarks are extracellular senile plaques and intracellular neurofibrillary tangles (NFTs), formed by aggregation of amyloid β-42 (Aβ-42) and Tau protein respectively. Aβ-42 is a transmembrane protein, which is produced after the sequential action of β- and γ-secretases, thus obtained peptide is released extracellularly and gets deposited on the neuron forming senile plaques. NFTs are composed of microtubule-associated protein-Tau (MAPT). Tau protein’s major function is to stabilize the microtubule that provides a track on which the cargo proteins are shuttled and the stabilized microtubule also maintains shape and integrity of the neuronal cell. Tau protein is subjected to various modifications such as phosphorylation, ubiquitination, glycation, acetylation, truncation, glycosylation, deamination, and oxidation; these modifications ultimately lead to its aggregation. Phosphorylation is the major modification and is extensively studied with respect to Tau protein. Tau protein, however, undergoes certain level of phosphorylation and dephosphorylation, which regulates its affinity for microtubule and ultimately leading to microtubule assembly and disassembly. Our main aim was to study the native state of longest isoform of Tau (hTau40WT-4R2N) and its shortest isoform, (hTau23WT-3R0N), at various temperatures such as 10, 25, and 37 °C. Raman spectroscopic results suggested that the proportion of random coils or unordered structure depends on the temperature of the protein environment. Upon increase in the temperature from 10 to 37 °C, the proportion of random coils or unordered structures increased in the case of hTau40WT. However, we did not find a significant effect of temperature on the structure of hTau23WT. This current approach enables one to analyze the global conformation of soluble Tau in solution.